ANALISA PENGARUH BEBAN MUATAN KENDARAAN BERLEBIH TERHADAP UMUR PERKERASAN JALAN GUSIG – SP3 BLUSUH - KHOIRONI, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2018)
Road damage occurring faster than the designed life is common. One reason is the burden of excessive loads on trucks. Impact on the overloaded axle load exceeds the load requirements as permitted by the Directorate General of Land Transportation. Through this study analyzed the extent of road damage caused by the percentage increase in cargo trucks that resulted in the charge which exceeds the limit allowed. The research location is in gusiq – sp3 blusuh. Data traffic is calculated for the expected design life of 10 years, so it can be seen a thick flexible pavement using the methods of Bina Marga. From the results of the study can be seen that the addition of excess charges up to 30% will reduce the design life of pavement up to 48%. But if there istransfer of 2as truck to the truck that has a number of axes more it will slow the damage